(untitled) - Liang, Hong (London, 2004)
Illustrating their intersecting role in manufacturing and technological development, this book examines tribological principles and their applications in CMP, including integrated circuits, basic concepts in surfaces of contacts, and common defects as well as friction, lubrication fundamentals, and the basics of wear. The book concludes its focus with mechanical aspects of CMP, pad materials, elastic modulus, and cell buckling. As the first source to integrate CMP and tribology, Tribology in Chemical-Mechanical Planarization provides applied scientists and engineers in the fields of semiconductors and microelectronics with clear foresight to the future of this technology
Keywords: Tribology,Grinding and polishing